PERENCANAAN ARSITEKTUR SISTEM INFORMASI PADA KANTOR KESEHATAN PELABUHAN JAMBI MENGGUNAKAN TOGAF ADM - Lies Aryani; Setiawan Assegaff (Jurnal Manajemen Sistem Informasi, 2017)
The application of information technology in the organization or company is not easy to do. Requiresgood planning, co-operation between the elements are compact, strong desire to change and inaccordance with the vision and mission of the organization to be applied. Kantor Kesehatan PelabuhanJambi is an institution of service for the community. At the Port Health Office use the computerinformation technology as tools still work, and use multiple systems are not integrated among units thatcan not share data or use data together between the units part of the existing work in the KantorKesehatan Pelabuhan Jambi .Therefore we need a plan that can describe an enterprise architecture. Todo enterpise architecture design required a complete methodology and easy to use, TOGAF ADM as oneof the methods that can be used to perform the design of enterprise architecture. Each stage of theTOGAF ADM can be carried out correctly if the existing business processes within the organizationreally should be understood and able to be assessed completely and correctly. This enterprisearchitecture modeling, provide guidance in making a blueprint for the development of informationsystems to the data, applications, business and technology. For the modeling of enterprise architecturecan dijadian initial step guide to planning and making the blueprint for the development of informationsystems at the later can be used by an organization to achieve its strategic objectives.